South Asia Nutrition Knowledge Initiative: Abstract digest October 2024 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
In the fourth edition of the South Asia Nutrition Knowledge Initiative’s Abstract Digest, we present global, regional, and country-level evidence on various aspects of nutrition. The global studies include a discussion on strategies to improve infant and child survival rates that are currently off track, a systematic review examining effects of small-quantity lipid-based nutrient supplements on maternal and infant outcomes, a scoping review to understand delivery platforms for reaching adolescents with nutrition interventions, a study assessing sugar-sweetened beverage consumption trends among children and adolescents across 185 countries, and a policy-oriented study shedding light on the cost to inaction in achieving nutrition targets. Other studies of interest include assessment of factors associated with adolescent motherhood and child undernutrition in Bangladesh, double and triple-burden of malnutrition among adolescents and children in India, and two sub-national level studies from India on diets and nutritional status of women of reproductive age, and women’s empowerment and child anthropometry. This issue also includes several studies on antenatal care, including its quality, utilization, and integration of other services to improve child growth, and two studies are focused on factors affecting dietary behaviors, and diet quality of women and children. Please scroll down to explore the abstracts of these studies. If you received this Abstract Digest via forwarding, we invite you to subscribe for future editions.